Can COPD Exacerbations Be Picked Up Early via a Weekly Medication Question Through a Smartphone Application? - Blondeel, Astrid; Demeyer, Heleen; Breuls, Sofie; Wuyts, Marieke; Glorie, Lies; De Maeyer, Nikolaas; Janssens, Wim; Troosters, Thierry (Frontiers in Rehabilitation Sciences, 2022)
Background Exacerbations affect the disease trajectory of patients with COPD and result in an acute drop of functional status and physical activity. Timely detection of exacerbations by non-medical healthcare professionals is needed to counteract this decline. The use of digital health applications in patient interaction allows embedded detection of exacerbations. However, it is unknown if this is an effective way to pick up exacerbations. Method We investigated the detection of exacerbations in patients with COPD enrolled in a physical activity coaching program, by prompting a weekly question on changes in medication via the smartphone application. Data on response rate and occurrence of exacerbations were collected. Results Response rate to the medication question, evaluated in 42 patients, was 72% (n=497). A change in medication was reported through the smartphone application in 38 (7.6%) of the answered questions. The response rate was significantly lower at 6 months follow-up compared to the first month (p=0.03). When evaluating the occurrence of adverse events in a subset of patients who completed 6 months of follow-up (n=27), 18 exacerbations were registered in 8 patients, of which 10 of these exacerbations (56%) were picked up by the medication question in the coaching application. Conclusion Electronic interaction through a weekly medication question, embedded in a smartphone application, is feasible to support the detection of the occurrence of COPD exacerbations and can be used complementary to regular forms of detecting exacerbations. Compliance and smartphone literacy should be optimized when further using this method to report on COPD exacerbations.